Insulation Panel Using a Combination of Rice Husk and Sugarcane Bagasse for Acoustic and Thermal Properties - Bidin, Normala; Kamarul Aini Mohd. Sari (Progress in Engineering Application and Technology, 2025)
Ensuring thermal comfort and mitigating noise pollution have emerged as two of the most critical challenges modern societies have had to confront and address in the design and operation of buildings and infrastructure. Within the past year, the use of agricultural waste as thermal insulation and sound absorption has garnered attention from researchers due to its properties. This study serves as an investigation of sugarcane bagasse and rice husk, which will be utilized as an insulation panel. The panels were produced using a hot press machine, ensuring uniformity and consistency in the material structure. The performance of the developed insulation panels will be investigated using the thermal conductivity apparatus, SOLTEQ MODEL HE:110, and Impedance Tube tests, respectively. Thermal conductivity values and sound absorption coefficient were measured and tabulated into graphs by using Microsoft Excel. Findings on the study found that Sample B has the most optimum performance of thermal and acoustic, with k value and SAC of 0.0333 W/m°C and 0.101-0.923, respectively. This development highlights the potential of the sample panel made from RH and SCB to replace synthetic panels currently available in the market.